Influence of the apparent density on the shrinkage of 43 tropical wood species - Fabrício Moura Dias; Tiago Hendrigo de Almeida; Victor Almeida De Araújo; Tulio Hallak Panzera; André Luis Christoforo; Francsico Antonio Rocco Lahr (Acta Scientiarum: Technology, 2019)
Recently, more wood species are gaining space in market. Hence, it is important to enlarge the utilization of non-traditional woods, which shall be able to replace the most popular species, provided that similar performances are respected. In contrast, the sustainable exploitations of natural resources by timber producers demand alternatives to exchange the use of restricted or blocked tropical wood species (e.g. Araucaria angustifolia) by other timbers, which are liable for commercial certification. This research, based on the test results obtained according to the Brazilian Standard prescriptions (NBR-7190 - Annex B), aimed at evaluating the influence of the apparent density on radial and tangential shrinkages, considering the results for forty-three Brazilian tropical wood species. Usually, this parameter is regarded as necessary to define the timber species to different applications. The results showed low dependence among those variables, considering the information from the literature.